EFFECT GIVING OF WATER EXTRACTS OF KELOR LEAF (Moringa oleifera) THROUGH DRINKING WATER ON PHYSICAL QUALITY OF LOHMANN BROWN CHICKEN EGGS AT 22-30 WEEKS OLD - I G. A. R., Atmaja; Bidura, I G. N. G.; Warmadewi, D. A. (Jurnal Peternakan Tropika, 2018)
This study aims to determine the effect of giving kelor ( Moringa oleifera ) leaf water extract ( Moringa oleifera ) through drinking water on the physical quality of Lohmann Brown chicken eggs at 22-30 weeks old. This research was conducted at farmer's chicken houses in DajanPeken Village, Tabanan District, Bali for 3 months. The design used in this study was Completely Randomized Design (RAL) with three treatments and six replications. Each replication (experimental unit) used two laying hens at 22-30 weeks old with a homogeneous weight. Treatment consisted of drinking water without addition of Moringa leaf water extract as control (Treatment A), drinking water with addition of 3% Moringa leaf water extract (Treatment B), drinking water with addition of 6% Moringa leaf water extract (Treatment C). The variables observed in this study were egg weight, percentage of egg white weight, weight percentage of egg yolk, percentage of skin weight, and skin thickness. The results showed that egg weight, egg yolk percentage, and weight percentage of egg shell, with addition of Moringo leifera water extract of 3% and 6% through drinking water which gave significant effect (P <0.05) increased and shell thickness which gave no significant effect (P> 0.05) also increased. In contrast, the percentage of egg white weight decreased compared to the chicken which was not given the addition of Moringa leaf water extract (Treatment A) as the control group. Based on the results of this study it can be concluded that the addition of Moringa oleifera water extract as much as 3% and 6% through drinking water can increase egg weight, egg yolk percentage, eggshell percentage and eggshell thickness on the contrary there is a decrease of percentage weight of egg whitesof Lohmann Brown chicken at 22-30 weeks old. Keyword s : Lohmann Brown chicken, extract kelor leaf, egg quality